Kepribadian dan Gaya Komunikasi Al-Mala' dalam Alquran dan Hadist - Lubis, Abdul Haris; Abdullah, Abdullah; Sikumbang, Ahmad Tamrin (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2025)
This paper examines Al-Mala''s personality and communication style in the Koran and Hadith. Al-Mala''s personality in the Qur'an and hadith is often described with negative traits, such as arrogance, injustice, rejection of the truth, and oppression of the weak. Their communication style is usually full of sarcasm, insults, and attempts to maintain the status quo. In this context, the communication of these officials is more manipulative and destructive, compared to communication that is soothing and reconciling. Al-Mala''s attitude shows how social position and power can influence a person's attitude and way of communicating, often by turning a deaf ear to the truth that comes from outside.